Review Artikel : Implementasi dan Evaluasi Peresepan Elektronik Dalam Upaya Menurunkan Kesalahan Pengobatan - Kholifatul Ulum; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Medication errors have unexpected effects and are even estimated to impact death significantly. Medication errors can occur in every treatment process, one of which is in the prescribing process. Electronic or e-prescribing is believed to have better effectiveness than manual prescription and is considered significant in reducing medication errors. Implementing e-prescribing has not been going well, especially in Indonesia, and requires evaluation and solutions to get the best health services and provide patient treatment safety. The method used is a literature review with online journal searches published from 2013 to 2021 on the Garuda, Science Direct, and PubMed databases. After the review process, ten journals were assigned for this review. Eight articles state that e-prescribing provides significant benefits and improves patient safety. Meanwhile, two studies reported that there was no significant difference between manual prescriptions and electronic prescriptions. Electronic prescriptions can improve patient care and medication safety by eliminating errors in handwriting, providing access to the patient's prescription history and drug allergies, safety, and speeding up patient waiting times. However, the implementation of e-prescribing has not yet fully worked out due to the lack of human resources, e-prescribing applications, and unsupported facilities.